Reduction of the subacromial space in athletes with and without rotator cuff tendinopathy and its association with the strength of scapular muscles. Issue 12 (December 2016) - Leong, Hio Teng; Tsui, Sammi Sin Mei; Ng, Gabriel Yin-fat; Fu, Siu Ngor
Abstract: Objectives : To compare the reduction of subacromial space (SAS) during arm abduction between overhead athletes with and without rotator cuff (RC) tendinopathy, and to explore the relationship between the strength of scapular muscles with the SAS. Design : Cross-sectional study. Methods : Sixty-six athletes (33 healthy and 33 with RC tendinopathy, mean age = 22.3 years) participated in the study. Ultrasound measurement of the SAS with arm at 0°, 30° and 60° of shoulder abduction were taken, and the maximal isometric force in upper, middle and lower trapezius, and serratus anterior with manual muscle tests (MMT) were assessed using a handheld dynamometer. The change in SAS during arm abduction from 0° to 30° (SAS0°–30° ), 30° to 60° (SAS30°–60° ) and 0° to 60° (SAS0°–60° ) was compared between groups. Differences in force produced with scapular muscles MMT between groups and relationships with reduction in SAS were explored. Results : We found more reduction of the SAS during SAS0°–30° in athletes with RC tendinopathy (0.44 ± 1.22 mm) than healthy athletes (−0.06 ± 1.41 mm) ( p  = 0.045). Athletes with RC tendinopathy demonstrated significant decrease in all scapular muscles MMT strength when compared to their healthy counterparts ( p  < 0.05). In healthy athletes, a lower middle and lower trapezius MMT strength were moderately associated with a greater reduction in SAS during 0° to 30° ( r  = −0.445, p  = 0.016 and r  = −0.423, p  = 0.022, respectively) and 0° to 60° of shoulder abduction ( r  = −0.415, p  = 0.018 and r  = −0.504, p  = 0.003, respectively). Conclusions : Athletes with RC tendinopathy demonstrated more reduction in the SAS during early arm abduction. Decreased strength of middle and lower trapezius was related to reduction of the SAS.